2004
DOI: 10.1124/jpet.103.062646
|View full text |Cite
|
Sign up to set email alerts
|

E-Prostanoid (EP)2/EP4 Receptor-Dependent Maturation of Human Monocyte-Derived Dendritic Cells and Induction of Helper T2 Polarization

Abstract: Prostaglandin (PG) E 2 induces dendritic cell maturation in cooperation with proinflammatory cytokines [such as tumor necrosis factor (TNF)-␣ and interleukin (IL)-1␤]. To clarify the involvement of E-prostanoid (EP) receptors in the effect of prostaglandin E 2 on human monocyte-derived dendritic cell (MoDC) maturation, we examined the effect of four types of EP receptor-selective agonists on MoDC maturation. PGE 2 as well as 11,15-O-dimethyl prostaglandin (E 2 ONO-AE1-259-01) (EP2 receptor agonist) and ONO-AE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 39 publications
7
50
2
Order By: Relevance
“…It is well established that PGE 2 mediates its inhibitory effect on the TLR-ligand-induced IL-12 production via the G ␣s -coupled receptors EP2 and EP4 (24), and our present data are in good agreement with these findings, although the pronounced cAMP response to Bet.-APE probably cannot be ascribed to an activation of EP2 and EP4 alone. PPE 1 , but not PPF 1 were able to inhibit IB␣ degradation in the cytoplasm, p65 translocation to the nucleus and NF-B binding to B binding sites on the DNA.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is well established that PGE 2 mediates its inhibitory effect on the TLR-ligand-induced IL-12 production via the G ␣s -coupled receptors EP2 and EP4 (24), and our present data are in good agreement with these findings, although the pronounced cAMP response to Bet.-APE probably cannot be ascribed to an activation of EP2 and EP4 alone. PPE 1 , but not PPF 1 were able to inhibit IB␣ degradation in the cytoplasm, p65 translocation to the nucleus and NF-B binding to B binding sites on the DNA.…”
Section: Discussionsupporting
confidence: 83%
“…To date, the uptake, receptor employment or signaling pathways of PPE 1 in cells of the human immune system are unknown, which prompted us to analyze the mode of action of E 1 -phytoprostanes on human DCs. PGE 2 , a known modulator of DC function, inhibits the secretion of IL-12 p70 via activation of the E-series receptors EP2 and EP4 (24,25). EP2 and EP4 signal via activation of adenylyl cyclase and the induction of cAMP (26).…”
mentioning
confidence: 99%
“…These findings are consistent with a functional interaction between the EP1 and EP4 receptors. Although the precise mechanism(s) involved in this unexpected phenomenon remain speculative, one possibility is that EP1 receptor activity in endothelium contributes to EP4 receptor-dependent generation of vasodilators (e.g., nitric oxide), because both of these receptors have been identified in endothelial cells (43) and heterodimerization and crosstalk between prostanoid receptors has been suggested (44,45). PGE 2 is a major COX product of vascular smooth muscle, and Ang II stimulates its synthesis in this tissue (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…23 It has also been reported that PGE 2 acts on CD4 þ T cells directly to induce Th2 cytokines, such as IL-4 and IL-5, by inhibiting the production of Th1 cytokines, such as IFN-g and IL-2. [38][39][40] In this study, Th2 skewing of naïve T cells was observed in the co-cultures with allogeneic DCs in the presence of culture supernatants of HGFs stimulated via HLA-DQ molecules (DQ-sup). Similar results were also obtained when naïve T cells were co-cultured with allogeneic DCs cultured with DQ-sup during their TNF-a-dependent maturation process.…”
Section: Many Kinds Of Mesenchymal or Epithelial Bystander Cells Aroumentioning
confidence: 99%